Locus of Control and Marital Satisfaction: Couple Perspectives Using Australian Data - Wang-Sheng Lee; Terra McKinnish (Institute of Labor Economics (IZA), 2019)
We investigate the effect of own and partner locus of control (LOC) on marital satisfaction using household longitudinal data from Australia. We also examine how the evolution of marital satisfaction over time depends on LOC. LOC indicates whether one believes that one's outcomes are more under personal control (internal LOC) or more under the control of external forces such as luck, fate or powerful others (external LOC). LOC orientation likely affects spouses' perception of marital problems and their willingness to utilize relationship-maintenance strategies when marital problems arise. We find that more internal LOC is associated with higher marital satisfaction and that own LOC matters more for marital satisfaction than spouse's LOC. Couples in which the husband is more externally oriented experience declines in marital satisfaction over time relative to couples in which the husband is more internally oriented.
Keywords: D1; J12; 330; assortative matching; locus of control; marital duration; marital satisfaction